The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/nop/npz043
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin-based regimen in pediatric intracranial germ-cell tumors (IC-GCTs): effectiveness and ototoxicity

Abstract: Background Induction chemotherapy with carboplatin followed by radiotherapy has been used for many years for treating intracranial germ-cell tumors (IC-GCTs) in Thailand. The objective of this study was to assess treatment outcomes, focusing on survival and ototoxicity. Methods The outcomes of all patients with IC-GCT treated at Ramathibodi Hospital and the Prasat Neurological Institute between 2000 and 2017 were reviewed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Our study confirmed that irradiation combined with chemotherapy was a fundamental treatment to achieve outcomes, 6 , 29 , 30 and an independent risk factor for survival outcomes in pediatric ICGCTs. Worawongsakul 10 and Villano et al 20 reported significantly inferior outcomes among patients with ICGCTs treated without irradiation compared with those who undergoing irradiation. In the Western population, the 3-year PFS and OS of NGGCTs were 88% and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study confirmed that irradiation combined with chemotherapy was a fundamental treatment to achieve outcomes, 6 , 29 , 30 and an independent risk factor for survival outcomes in pediatric ICGCTs. Worawongsakul 10 and Villano et al 20 reported significantly inferior outcomes among patients with ICGCTs treated without irradiation compared with those who undergoing irradiation. In the Western population, the 3-year PFS and OS of NGGCTs were 88% and 93%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Carboplatin-based regimen instead of cisplatin followed by irradiation has been employed as a standard regimen for childhood ICGCTs in Thailand since 2013. Worawongsakul et al 10 reported an excellent OS of 96% and EFS of 94% for patients with ICGCTs treated with a carboplatin-based regimen with lower ototoxicity effects. They found that germinomas had higher OS and EFS but without statistical significance, similar to our report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the limitation of health care resources, protocols in LMIC should not only consider survival, but also feasibility. The treatment of malignant childhood brain tumours remains a challenge in LMIC as it requires a multidisciplinary team that may not available worldwide, such as access to chemotherapy, surgical expertise, supportive care and radiation facilities.Although the SIOP-CNS-GCT-96 strategy is followed by many countries across the world, the viability and survival outcome in theLMICsetting is not well described.Despite small series [20][21][22], there is a paucity of data to understand if this combined regimen would be considered a possible and practicable strategy outside the developed world. Here, we evaluate the outcome of a cohort of iGCT treated using the SIOP-CNS-GCT-96 approach prior to 2009 followed by the adoption of the North American approach of whole ventricular radiotherapy after 2009 at Hospital JP Garrahan in Buenos Aires.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the limitation of health care resources, protocols in LMIC should not only consider survival, but also feasibility. The treatment of malignant childhood brain tumours remains a challenge in LMIC as it requires a multidisciplinary team that may not available worldwide, such as access to chemotherapy, surgical expertise, supportive care and radiation facilities.Although the SIOP-CNS-GCT-96 strategy is followed by many countries across the world, the viability and survival outcome in theLMICsetting is not well described.Despite small series [20][21][22], there is a paucity of data to understand if this combined regimen would be considered a possible and practicable strategy outside the developed world. Here, we evaluate the outcome of a cohort of iGCT treated using the SIOP-CNS-GCT-96 approach prior to 2009 followed by the adoption of the North American approach of whole ventricular radiotherapy after 2009 at Hospital JP Garrahan in Buenos Aires.…”
Section: Introductionmentioning
confidence: 99%